Complexos de Cromo(III)-salen como catalisadores em reações de oxidação de sulfetos - Aranha, Pedro Esteves (Universidade Federal de São Carlos, 2009)
Transition metal complexes participate in many chemical processes. The study of these complexes is very interesting because of the diversified chemistry and great utility. Transition metal complexes act as catalysts in various homogenous and heterogeneous systems. The catalytic activity of these complexes is due to the presence of only one active metallic site for the catalytic reaction. Thus this type of reaction can be advantageous due to the elevated selectivity of the metal center. The new catalysts were characterized by melting point, elemental microanalyses, infrared and visible-ultraviolet spectra, molar conductance, magnetic susceptibility and mass spectra. The catalytic reaction of phenyl methyl sulfide to phenyl methyl sulfoxide and/or phenyl methyl sulfone was carried out in flasks, under agitation and temperature control, the progress of the reaction was monitored by gas chromatography. The catalytic results for reactions of oxidation of sulfide presented yields above 48% with PhIO as oxidant. Twelve catalysts were tested where four of them oxidizes successfully phenyl methyl sulfide into phenyl methyl sulfoxide. Specially the complex [Cr(3,5-Isalen)(H2O)2]Cl that yields 98.2% in this reaction. Another complexes tested had good results in the first hours of reaction but led to formation of sulfone after some time of reaction. It was observed that complexes containing only electron donor substituents groups para to hydroxyl of phenolic ring and complexes with esteric substituents groups ortho and para to hydroxyl of phenolic ring presented more selectivity as catalyst for the reaction of oxidation of sulfide.
Keywords: Complexos metálicos; Cromo; Schiff, Bases de; Catálise - oxidação; Sulfóxido; CIENCIAS EXATAS E DA TERRA::QUIMICA